An evaluation of the 'Circle of Friends' intervention used to support pupils with autism in their mainstream classrooms - James, Rebecca (2011)
This study is an evaluation of the 'Circle of Friends' (CoF) intervention used to support five pupils with a diagnosis of autism (the focus pupils) in their mainstream classrooms. Relevant theory and existing research is outlined before the study is described. A single case experimental design is used to evaluate the impact of the CoF intervention on the focus children's level of social inclusion (calculated from peer ratings). Results suggest that the CoF whole class meeting had an initial positive impact on all focus children's levels of peer acceptance and rejection. During the course of weekly CoF meetings, however, results suggest that this level of change was not maintained. For four of the five focus children, levels of peer acceptance and rejection generally returned to levels comparable to those observed prior to the start of the intervention. The study also reports some changes in measures taken before and after the CoF intervention. For four out of the five cases, a positive change in the focus children's happiness was observed. For three out of the five cases generally positive changes in adults' ratings of the focus children's behaviour were observed. In an attempt to understand how the CoF intervention works, attributions made by peers about one of the focus children's behaviour were explored before and after the CoF intervention though no clear overall change following the intervention was found. The results reported are examined in relation to the theory and research outlined in the Literature Review and the design, measures and procedures described in the Methodology. Limitations of the research are discussed and implications for practice and future research outlined.